Differentiation of movement behaviour in an adaptively diverging salamander population. Issue 22 (16th October 2017) - Hendrix, Ralf; Schmidt, Benedikt R.; Schaub, Michael; Krause, E. Tobias; Steinfartz, Sebastian
Abstract: Dispersal is considered to be a species‐specific trait, but intraspecific variation can be high. However, when and how this complex trait starts to differentiate during the divergence of species/lineages is unknown. Here, we studied the differentiation of movement behaviour in a large salamander population ( Salamandra salamandra ), in which individual adaptations to different habitat conditions drive the genetic divergence of this population into two subpopulations. In this system, salamanders have adapted to the deposition and development of their larvae in ephemeral ponds vs. small first‐order streams. In general, the pond habitat is characterized as a spatially and temporally highly unpredictable habitat, while streams provide more stable and predictable conditions for the development of larvae. We analysed the fine‐scale genetic distribution of larvae, and explored whether the adaptation to different larval habitat conditions has in turn also affected dispersal strategies and home range size of adult salamanders. Based on the genetic assignment of adult individuals to their respective larval habitat type, we show that pond‐adapted salamanders occupied larger home ranges, displayed long‐distance dispersal and had a higher variability of movement types than the stream‐adapted individuals. We argue that the differentiation of phenotypically plastic traits such as dispersal and movement characteristics can be a crucial component in the course of adaptation to new habitat conditions, thereby promoting the genetic divergence of populations.